2021
DOI: 10.26434/chemrxiv.14039141.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Production of High Value Amine Intermediates via Biocatalytic Cascades in Continuous Flow

Abstract: <div> <p>A key aim of biocatalysis is to mimic the ability of eukaryotic cells to carry out compartmentalized multistep cascades in a controlled and selective way. As biocatalytic cascades get longer and more complex, reactions become unattainable under typical batch conditions. Here a continuous flow multipoint injection reactor was combined with switching valves to overcome batch incompatibility, thus allowing for successful biocatalytic reaction cascades. As proof-of-principle, several reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…191 Compartmentalization of reactions permitted by flow chemistry enables reactions that would otherwise be unfeasible. In a striking example, Mattey et al 192 demonstrated the synthesis of primary and secondary amines using flow chemistryincluding 4′-O-methylnorbelladine, a precursor for pharmacologically active alkaloid scaffolds such as the dementia drug galantamine. It involves the use of a galactose oxidase (GO) to convert alcohols to the starting aldehydes, and then either a transaminase to generate primary amines, or a reductive aminase (ReAm/IRED) (combined with a NADPH regenerating GDH) for secondary amines.…”
Section: Could Bementioning
confidence: 99%
“…191 Compartmentalization of reactions permitted by flow chemistry enables reactions that would otherwise be unfeasible. In a striking example, Mattey et al 192 demonstrated the synthesis of primary and secondary amines using flow chemistryincluding 4′-O-methylnorbelladine, a precursor for pharmacologically active alkaloid scaffolds such as the dementia drug galantamine. It involves the use of a galactose oxidase (GO) to convert alcohols to the starting aldehydes, and then either a transaminase to generate primary amines, or a reductive aminase (ReAm/IRED) (combined with a NADPH regenerating GDH) for secondary amines.…”
Section: Could Bementioning
confidence: 99%